2016
DOI: 10.1177/1359105316676328
|View full text |Cite
|
Sign up to set email alerts
|

Obese children are thin in parents’ eyes: A psychologically, socially, or culturally driven bias?

Abstract: Although obesity presents a serious health problem in children, parents often underestimate their children's overweight and obesity status. Therefore, scientific literature was systematically screened through PubMed and PsycINFO to demonstrate the psychological, social, and cultural processes that underlie this evaluation bias. A total of 37 papers that focused on research conducted in different geopolitical contexts were taken into account. Furthermore, a lexicometric analysis of the papers' conclusions was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 47 publications
3
21
1
Order By: Relevance
“…A high percentage of mothers underestimated the nutritional status of their overweight children (39,3%), a trend that has been previously observed among parents of this population [8,7,12,13,14,31,32]. However, contrary to previous findings, 29.9% of mothers of overweight children and 47.9% of those of obese children overestimated the nutritional status of their child.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…A high percentage of mothers underestimated the nutritional status of their overweight children (39,3%), a trend that has been previously observed among parents of this population [8,7,12,13,14,31,32]. However, contrary to previous findings, 29.9% of mothers of overweight children and 47.9% of those of obese children overestimated the nutritional status of their child.…”
Section: Discussioncontrasting
confidence: 84%
“…Hochdorn et al [14] verified in a systematic review that this occurs globally, and that most of the studies carried out in Latin America, East Asia and Europe noted underestimation of the nutritional status of overweight and obese children. Furthermore, many mothers believe that childhood overweight is a sign of good health and that overweight will be resolved later as the child grows [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hochdorn et al, 41 who reviewed 37 papers that focused on research conducted in different geopolitical contexts, similarly concluded that adequate educational support for promoting parents' awareness and their realistic recognition of their children's weight should be implemented in all healthcare policies addressing childhood obesity. Duarte et al, 21 further suggested attendance at well-child visits may be an effective way to decrease inaccuracies in maternal child weight judgments, and again reinforced the importance of incorporating the influence of salient health professionals from the earliest point in time in childhood obesity prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, research continues to show parents commonly underestimate the weight status of overweight or obese children, regardless of country of origin, as outlined by Regber et al, 41 in a study of eight countries in Europe 44 and Musaad et al, 45 in an American based study where 93% of youth were not correctly perceived as overweight or obese by the parent. Another issue is that accurate parental perceptions of child weight may counter intuitively contribute to obesity.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are not new and have long been presumed to be a concern; if people do not realise they are overweight, how will they change their behaviour to lose weight? For example, the failure of parents to identify their children as overweight has recently been described as 'promoting the silent rise' of obesity, 1 and new research reported in the International Journal of Obesity suggests that healthcare professionals not notifying children and their families of their 'unhealthy weight status' is a missed opportunity to combat obesity. 2 These sentiments are echoed in public health intervention approaches.…”
mentioning
confidence: 99%